A zebrafish larval model for drug-induced hepatic Injury due to first-line antituberculosis drugs and possible prevention/treatment with N-acetyl-cysteine - Motha, Khetiwe (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc) -- Stellenbosch University, 2022.